2016
DOI: 10.1093/gbe/evw103
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Duplications Shaped the Receptor Tyrosine Kinase Repertoire of Jawed Vertebrates

Abstract: The receptor tyrosine kinase (RTK) gene family, involved primarily in cell growth and differentiation, comprises proteins with a common enzymatic tyrosine kinase intracellular domain adjacent to a transmembrane region. The amino-terminal portion of RTKs is extracellular and made of different domains, the combination of which characterizes each of the 20 RTK subfamilies among mammals. We analyzed a total of 7,376 RTK sequences among 143 vertebrate species to provide here the first comprehensive census of the ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 117 publications
1
24
0
Order By: Relevance
“…Other RTKs, namely, PDGFR-b (Wang et al, 2012), fibroblast growth factor receptor (FGFR; Fujita-Hamabe et al, 2011), and Ephrin receptor (EphB; Liu et al, 2011), have been shown to modulate morphine analgesic tolerance. These RTKs are closely phylogenetically related to the EGFR (Brunet et al, 2016). Thus, RTK signaling could play a prominent role in Figure 5.…”
Section: Discussionmentioning
confidence: 98%
“…Other RTKs, namely, PDGFR-b (Wang et al, 2012), fibroblast growth factor receptor (FGFR; Fujita-Hamabe et al, 2011), and Ephrin receptor (EphB; Liu et al, 2011), have been shown to modulate morphine analgesic tolerance. These RTKs are closely phylogenetically related to the EGFR (Brunet et al, 2016). Thus, RTK signaling could play a prominent role in Figure 5.…”
Section: Discussionmentioning
confidence: 98%
“…While the specific deficit of dendrite regeneration in Ror mutants could be due to increased demands on nucleation that surpass a phenotypic threshold only after dendrite injury, the fact that Ror is a signaling receptor raises the intriguing possibility that it could also respond to injury signals. The closest phylogenetic neighbors to the Ror family of RTKs are the tropomyosin receptor kinases (Trks) [69], which have been lost in evolution in flies and worms [70,71]. One major function of Trk receptors is to couple neuronal survival to target innervation.…”
Section: Discussionmentioning
confidence: 99%
“…Three receptors of the INSR (insulin receptor) subfamily are known in vertebrates: IGF1R (insulin-like growth factor 1 receptor), INSR (insulin receptor) and INSRR (insulin receptor-related receptor) (Brunet et al, 2016). These receptors are characterized by the presence in their ectodomain of two L-domains separated by a furin-like cysteine rich region and followed by three fibronectin type III domains (Adams et al, 2000).…”
Section: Insulin Receptormentioning
confidence: 99%